2023
DOI: 10.1128/iai.00029-23
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals Unique Alterations in the Immune Panorama and Treg Subpopulations in Mice during the Late Stages of Echinococcus granulosus Infection

Abstract: Cystic echinococcosis (CE) is a common zoonotic parasitic disease that seriously impacts public health. However, the full spectrum of immune cell changes in Echinococcus granulosus infection, especially the negative immune regulation of subpopulations of regulatory T (Treg) cells, are not yet well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Extensive research indicates that helminths use small microRNAs to manipulate their host’s immune responses by ‘cross-kingdom’ gene regulation ( Chowdhury et al, 2023 ). Advances in single-cell sequencing have significantly clarified the influence of the impact of Echinococcus on the immune microenvironment of the host ( Yasen et al, 2021 ; Jiang T. et al, 2022 ; Jiang X. et al, 2022 ; Wu et al, 2023 ). The second aspect addresses the effects of host on the parasite, including adapting to host microenvironment and evading host immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research indicates that helminths use small microRNAs to manipulate their host’s immune responses by ‘cross-kingdom’ gene regulation ( Chowdhury et al, 2023 ). Advances in single-cell sequencing have significantly clarified the influence of the impact of Echinococcus on the immune microenvironment of the host ( Yasen et al, 2021 ; Jiang T. et al, 2022 ; Jiang X. et al, 2022 ; Wu et al, 2023 ). The second aspect addresses the effects of host on the parasite, including adapting to host microenvironment and evading host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite–host interaction could be divided into two equal important aspects. Whereas most studies have focused on the effects of parasite on the host ( Yasen et al, 2021 ; Jiang T. et al, 2022 ; Jiang X. et al, 2022 ; Wu et al, 2023 ), relatively few studies have been reported concerning the effects of host on the parasite ( Hemer et al, 2014 ; Cheng et al, 2017 ). The most important impact of host on the parasite is immune response and the oxidative stress it induces.…”
Section: Introductionmentioning
confidence: 99%
“…After washing, the samples were blocked with 5% BSA and incubated at room temperature for 1 h with the secondary antibody. Samples were then incubated in the dark with 10 μg/mL DAPI (Servicebio Technology Co., Ltd., China) in PBS for 10 min at room temperature, washed three times with PBS and mounted with Vectashield mounting medium (Vector Labs) [23, 24]. Images were acquired on a Nikon A1 confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The fast-developing field of single-cell technologies have brought mechanistic insights into the host–pathogen interactions that influence viral ( 34 ), bacterial ( 35 ), fungal ( 36 ), and parasitic infections ( 37 ). In this study, we performed single-cell RNA-Seq (scRNA-Seq) analysis with murine splenocytes infected with green fluorescent protein expressing Bb (GFP+ Bb ) and compared the cellular and molecular patterns between Bb infected (GFP-positive) and bystander (GFP-negative) splenocytes.…”
Section: Introductionmentioning
confidence: 99%